Postictal status and clinical variables in adults with epilepsy - Agostinho, Cecília Fusco; Tedrus, Glória M. A. S. (Arquivos de Neuro-Psiquiatria, 2025)
Symptoms in the postictal period are often neglected by professionals and patients/family members.To relate the characteristics of the postictal period with the clinical variables of adult patients with epilepsy.Prospectively, the clinical characteristics of the postictal period were related to the clinical variables and the scores on the Hospital Anxiety and Depression Scale (HADS) and Mini-Mental State Examination (MMSE) of 70 patients with epilepsy.The mean age was 47.6 years old, and 34 (48.6%) patients were male, the mean age at onset of epilepsy was 20.3 years old, the epileptic syndrome was structural in 48 cases, the mean score in the MMSE was 23.6, the mean score in the HADS-anxiety was 7.3, and in the HADS-depression it was 5.6. Postictal manifestation occurred in 59 (84.2%) cases, with prolonged duration in 22 (37.2%) cases. There was a difference in the duration and presence of postictal manifestation according to age at the onset of epilepsy. Higher HADS-anxiety scores were associated with the presence of confusion in the postictal period (t-test; 9.3 ± 6.8 versus 5.8 ± 4.8; p = 0.015). Lower MMSE scores were related to postictal anxiety and sleepiness/headache/confusion. Left-sided epileptiform activity (EA) was associated with postictal sleepiness/headache/confusion. There was a difference in postictal manifestation according to epileptic syndrome.The characteristics of the postictal period differed according to the age of onset, the type of seizure, and the epileptic syndrome. Different symptoms in the postictal period were associated with the scores on HADS anxiety, MMSE, and left-sided EA on the electroencephalogram.
Keywords: Epilepsy; Seizures; Confusion